1998
DOI: 10.1038/sj.jhh.1000607
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of silent myocardial ischaemia in patients with white-coat hypertension

Abstract: The aim of this study was to estimate the incidence of silent myocardial ischaemia in patients with mild to moderate hypertension, white-coat hypertension (WCH) and those with normal blood pressure. Ambulatory electrocardiographic (ECG) monitoring was carried out in 272 cases with normal blood pressure, 164 cases with mild to moderate hypertension (diastolic blood pressure Ͼ95 and Ͻ114 mm Hg), and 106 cases with white-coat hypertension who were diagnosed with ambulatory blood pressure monitoring. The ages of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…37 Incidence of SMI was observed to be 26.2% in hypertensive patients and 18.8% in white-Coat hypertension. 38 Our findings related to systolic and diastolic blood pressure did not show that there was a significant difference in diabetic patients, with or without SMI; thus, in the present study SMI was not affected by the hypertensive status of the patients.…”
Section: Discussionmentioning
confidence: 39%
“…37 Incidence of SMI was observed to be 26.2% in hypertensive patients and 18.8% in white-Coat hypertension. 38 Our findings related to systolic and diastolic blood pressure did not show that there was a significant difference in diabetic patients, with or without SMI; thus, in the present study SMI was not affected by the hypertensive status of the patients.…”
Section: Discussionmentioning
confidence: 39%
“…Patients with white coat hypertension not only show greater blood pressure variability than normal control subjects, but also have a different metabolic and neuroendocrine profile 90. Some investigators reported that patients with white coat hypertension have moderately increased left atrial dimension91 and left ventricular mass,88 91disturbed diastolic function of the left ventricle91 or an increased prevalence of silent coronary ischaemia 92. On the other hand, there is mounting evidence (already discussed) that apart from the few cases misclassified at initial diagnosis, outcome is better correlated with ambulatory blood pressure measurements than with clinic readings47 68 72-76 78 and that white coat hypertension, therefore, is genuinely a benign condition.…”
Section: Diagnosis and Treatment Of White Coat Hypertensionmentioning
confidence: 99%
“…Nalbantgil et al [40] estimated the incidence of silent myocardial ischemia by ambulatory electrocardiographic monitoring in patients with mild-to-moderate hypertension, white-coat hypertension and those with normal blood pressure, stating that the incidence of silent ischemia was 6.4%, 18.8%, and 26.2% in cases with normal blood pressure, white-coat hypertension, and hypertension, respectively.…”
Section: Smi and Hypertensionmentioning
confidence: 98%